2012
DOI: 10.1590/s1519-99402012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Complexo homeopático na prevenção e tratamento de diarréias em leitões lactentes

Abstract: O trabalho foi realizado com o objetivo de comparar o potencial do antibiótico e de um complexo homeopático sobre a prevenção e tratamento de diarréia em leitões lactentes, bem como comparar e avaliar os resultados de desempenho e mortalidade durante a fase de aleitamento. Foram utilizadas 98 leitegadas, em um total de 988 leitões, de matrizes com ordem média de 5,92 ± 2,65 partos. As leitegadas foram distribuídas em delineamento experimental de blocos ao acaso, composto pelos tratamentos controle, antibiótico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…Se encontró un resultado similar en corderos lecheros alimentados con leche descartada (15). Ya en 2012, los investigadores descubrieron que un complejo homeopático a los lechones durante la fase de lactancia tenía una eficacia del 95.23% para prevenir la diarrea (13). Estos resultados, así como los presentados en el presente estudio, muestran que los productos homeopáticos pueden ser una excelente solución para minimizar o prevenir la diarrea en animales.…”
Section: Reporte De Casounclassified
See 1 more Smart Citation
“…Se encontró un resultado similar en corderos lecheros alimentados con leche descartada (15). Ya en 2012, los investigadores descubrieron que un complejo homeopático a los lechones durante la fase de lactancia tenía una eficacia del 95.23% para prevenir la diarrea (13). Estos resultados, así como los presentados en el presente estudio, muestran que los productos homeopáticos pueden ser una excelente solución para minimizar o prevenir la diarrea en animales.…”
Section: Reporte De Casounclassified
“…Para minimizar los impactos de la diarrea causada por Giardia sp., se han buscado productos alternativos, incluidos los preventivos y los productos curativos homeopáticos que tratan la diarrea (12). La prevención y el tratamiento de la enteritis con homeopatía en animales de granja han mostrado buenos resultados (13,14,15). Sin embargo, para las mascotas, no se han estudiado los efectos de los agentes antiparasitarios combinados con agentes homeopáticos para el tratamiento de Giardia.…”
Section: Introductionunclassified
“…Homeopathic products have been of benefit to various categories of animal in pig farming. Indeed, compared with antibiotics, HPs have been shown to improve performance and prevent diarrhoea in young pigs (Coelho et al, 2009;Kiefer et al, 2012). Moreover, they have been reported to reduce the number of animals with intestinal disorders, promote weight gain (Coelho et al, 2014), and improve the percentage and quality of meat and the marbling of the pig carcass.…”
Section: Introductionmentioning
confidence: 99%
“…19 When administered correctly, HP have been shown to be effective in the treatment and prevention of diarrhea in piglets, with greater efficiency than antibiotics. 20,21 When associated or not with biotherapy, they can reduce the number of animals with diarrhea and increase body weight gain. 22 Previously studies conducted with other species also reported that homeopathic combinations were able to improve carcass yield of poultry, 23 increase final body weight and carcass yield of steers, 24 improve growing, survival and immune function in juvenile scallops, 25 improve meat coloration, decrease stress and contribute to the welfare and quality of beef, 26 and exhibit higher polyunsaturated fatty acid/saturated fatty acid ratio than controls in Nile tilapia fish.…”
Section: Introductionmentioning
confidence: 99%